Kepemimpinan Ideal Di Era Generasi Millenial - Danang Nugroho; Alviani Maulida; Heni Rahayu; Hilma Jakiyah; Leni Yuliani; Luthvia Azzahra (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
In an organization it is very important to have leadership with all types of leadership. To achieve optimal performance in an organization, a leader is needed who is able to plan, place and organize his subordinates so that they lead to organizational goals. How leadership is implemented and how satisfied subordinates are influences leadership success. It is very important to create an effective leader in the current era and the future in the younger generation. Many leaders emerge over time as a result of the needs and environmental conditions at that time. To run an effective government in the era of the millennial generation, leaders need to have a reputation as leaders who are trustworthy, talented and have a clear vision. However, effective leaders must also be honest, fair, and loyal to the needs of society. The independence and entrepreneurial spirit of the millennial generation needs to be supported by millennial leadership. Independence and entrepreneurship are the main pillars of a country's development.